Commitment contracts - Gharad Bryan; Dean S. Karlan; Scott Nelson (Yale University, Economic Growth Center, 2009)
We review the theoretical and empirical literature on commitment devices. A commitment device is any arrangement, entered into by an individual, with the aim of making it easier to fulfill his or her own future plans. We argue that there is growing empirical evidence supporting the proposition that people demand commitment devices and that these devices can change behavior. We highlight the importance of further research exploring soft commitments those involving only psychological costs and the welfare consequences of hard commitments those involving actual costs especially in the presence of bounded rationality.
Keywords: D03; D14; 330; consumer/household economics; institutional and behavioral economics